Supporting athletes during a challenging situation: recommendations from a global insight of COVID-19 home-based training experience - Jad Adrian Washif; Florentina J. Hettinga; Achraf Ammar; Dina Christa Janse van Rensburg; Olivier Materne; Khaled Trabelsi; Mohamed Romdhani; Abdulaziz Farooq; David B. Pyne; Karim Chamari (BMC, 2024)
Abstract Background For athletes, overcoming obstacles in challenging situations like pandemic home training is crucial. Strategies and approaches in this context are not well-documented. Our study aims to investigate such a scenario from a performance standpoint, based on a major global crisis: the COVID-19 pandemic and lockdown. Methods This cross-sectional study surveyed athletes without disabilities using online questionnaires (35 languages) from May to July 2020. Questions included aspects of alternative routines, training monitoring, recovery, sleep patterns, injury occurrence/prevention based on structured answers, and an open-ended question on lockdown training experiences. Results Of the 11,762 athletes from 142 countries, 63% were male, including at World-Class, International, National, State and Recreational levels. During lockdown, 25% athletes used innovative or modern ways to maintain or improve fitness e.g., virtual reality and tracking devices (favoring World-Class level, 30%). Many athletes, regardless of gender (43%) watched video competitions to improve/maintain their mental skills and performance [World-Class (47%) and International (51%)]. Contact frequency between athletes and their coaches was mainly at least once a week (36%), more among higher-level (World-Class/International) than lower-level athletes (27 vs. 16%). Higher-level athletes (≥ 54%) monitored training load and were assisted by their coaches (21%). During lockdown, stretching (67%) was considered one of the primary means of recovery, especially for higher-level athletes (> 70%). Compared to pre-lockdown, about two-thirds of athletes reported "normal" or "improved" sleep quality and quantity, suggesting a low sleep quality pre-lockdown. On average, 40% utilized injury prevention exercises (at least) once a week [World-Class (51%) and International (39%)]. Most injury occurrences during lockdown involved the knee (18%), ankle (16%), and back (9%). Four key themes emerged regarding lockdown experiences: remote training adaptation (e.g., shifting training focus), training creativity (e.g., using household items), performance enhancement opportunities (e.g., refocusing neglected aspects), and mental and motivation challenges. Conclusions Both male and female athletes, particularly those of higher levels, displayed some adaptalibity during the COVID-19 lockdown, employing innovative approaches and technology for training. Many athletes implemented load monitoring, recovery, and attentive of injury prevention, while optimizing their sleep quality and quantity. Athletes demonstrated their abilities to navigate challenges, and utilized different coping strategies in response to the lockdown's constraints.